Exploration of the Synthetic Potential of 1,2-Oxazin-4-ones as Precursors of Enantiopure Amino Polyols - Wunderlich, Johannes; Rettig, Jonas; Mallia, Davide F.; Flieger, Richard C. F.; Hýrošovà, Eva; Bouché, Léa; Wiesner, Anja; Reissig, Hans-Ulrich; Zimmer, Reinhold (Synthesis, 2025)
The carbonyl group of two diastereomeric 1,2-oxazin-4-ones was employed to study routes to new enantiopure amino polyols. Addition of nucleophiles to the syn-configured diastereomer occurred with high stereoselectivity, whereas the reactions of the anti-configured 1,2-oxazine are less selective. Grignard reagents and an ester enolate were examined as nucleophiles. The carbonyl group of the 1,2-oxazin-4-ones could also be converted into an exo-methylene group by a Wittig reaction. The β-hydroxy esters derived from the ester enolate additions were treated with acid and provided bi- and tricyclic δ-lactones. Again, the configuration of the precursor compounds was crucial for the selectivity. Representative derivatives of the obtained products were either subjected to hydrogenolysis under palladium catalysis or treated with samarium diiodide as an N–O bond cleaving reagent. These reductions mostly provide the expected amino polyols. Two chain-elongated diastereomeric 1,2-oxazine derivatives bearing three contiguous stereogenic centers were also subjected to acidic conditions, which afford unique di- and tricyclic amino polyol derivatives.
Keywords: Addition of nucleophiles; Amino alcohols; δ-Lactone; Reduction; 1,2-Oxazine; Samarium diiodide